INOVASI TEKNOLOGI DALAM KURIKULUM MERDEKA - Zulkifli Zulkifli (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
The implementation of technological innovation in the Merdeka Curriculum plays a vital role as the main driver of educational transformation toward the Society 5.0 era. However, empirical realities still reveal practical gaps, including low socialization, immature preparation, teachers' limited digital literacy, and contradictory curriculum subject regulations. This study aims to analyze the application of the six axes of technological innovation in the Merdeka Curriculum, map teachers' structural barriers, and formulate its reconstructed meaning from the theological perspective of Islamic Religious Education (IRE). The research method employed is descriptive qualitative through library research with a content analysis model, utilizing theoretical literature and previous research studies published within the 2018–2026 range. The results indicate that the adoption of technological innovation positively contributes to realizing flexibility, personalized learning, and alignment with the modern working world (link and match). To address educators' digital literacy issues, the government must provide structural interventions through continuous and gradual training programs. From the IRE perspective, merdeka belajar is reconstructed as an internal transformative process based on human nature (fitrah) to lead individuals toward becoming complete human beings (insan kamil) by embedding the theological values of monotheism (tauhid) and the concept of ikhtiar (freedom of choice that contains goodness). The history of Islamic civilization proves that a liberating and interactive learning atmosphere successfully revives the spirit of curiosity without disciplinary boundaries to produce multitalented scholars who are resilient in the digital age.